When anxiety attacks - Koscik, Terian; Koscik, Terian (Singing Dragon, an imprint of Jessica Kingsley Publishers, 2016)
Terian Koscik shares her experiences of living with anxiety, and how going to a therapist taught her one of the most important things she could ever learn: there really is no "right" way to feel"--Cover page [4]